2006
DOI: 10.2746/042516406775374243
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic diagnosis and treatment of intra‐articular insertional injuries of the suspensory ligament branches in 18 horses

Abstract: Summary Reasons for performing study: Clinical association between the branches of insertion of the suspensory ligament (SL) and metacarpophalangeal (MCP) and metatarsophalangeal (MTP) joints has been reported. However, there has been no assessment of the lengths of the SL branches which are subsynovial with respect to the joints or reports of involvement of the MCP/MTP joints in injuries of the SL branches. Objectives: To establish proportions of SL branches subsynovial with respect to the MCP/MTP joints an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Although it has been suggested that some horses with clinical signs of SLB desmitis have no ultrasonographic evidence of fibre disruption , in most cases this is pivotal to lesion identification . In the cases reported, four abnormalities, increased cross sectional area, a defect in the palmar/plantar abaxial margin, extrusion of disrupted ligament fibres and adjacent layered echogenic tissue, were consistent features.…”
Section: Discussionmentioning
confidence: 81%
“…Although it has been suggested that some horses with clinical signs of SLB desmitis have no ultrasonographic evidence of fibre disruption , in most cases this is pivotal to lesion identification . In the cases reported, four abnormalities, increased cross sectional area, a defect in the palmar/plantar abaxial margin, extrusion of disrupted ligament fibres and adjacent layered echogenic tissue, were consistent features.…”
Section: Discussionmentioning
confidence: 81%
“…Approximately 30% of the branches of insertion of the suspensory ligament are subsynovial in the metacarpophalangeal/metatarsophalangeal joints (Minshall & Wright, 2006). Tears involving the dorsal surface of the suspensory ligament branches can result in articular deficits and extrusion of disrupted ligaments fibers into this synovial cavity.…”
Section: Avulsions Of the Suspensory Ligament Insertionsmentioning
confidence: 99%
“…Most occur at or close to the abaxial margins of the proximal sesamoid bones and appear to be avulsion injuries. Minshall & Wright (2006) described 18 cases with equal distribution between forelimbs and hindlimbs and between medial and lateral branches. All affected joints were distended.…”
Section: Avulsions Of the Suspensory Ligament Insertionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamm et al (2011) evaluated the influence of size and geometry of apical sesamoid fragments following arthroscopic removal in Thoroughbreds and found no relationship to racing performance. Because 30% of the branches of insertion of the suspensory ligaments are subsynovial in the metacarpophalangeal/metatarsophalangeal joints, tears involving their dorsal surfaces can result in articular deficits and extrusion of disrupted ligament fibers into the synovial cavity; it has now been documented that such cases can be successfully treated with arthroscopic debridement (Minshall and Wright, 2006).…”
Section: Arthroscopic Surgery In the Horse-advances Since 2005mentioning
confidence: 99%